GTApprox: Surrogate modeling for industrial design. (December 2016) - Belyaev, Mikhail; Burnaev, Evgeny; Kapushev, Ermek; Panov, Maxim; Prikhodko, Pavel; Vetrov, Dmitry; Yarotsky, Dmitry
Highlights: GTApprox is a new surrogate modelling tool aimed at engineering applications. GTApprox has a fully automated choice of the surrogate modelling method. GTApprox features tensor approximations, smart selection and other unique algorithms. GTApprox is shown to significantly outperform several popular alternative tools. Abstract: We describe GTApprox — a new tool for medium-scale surrogate modeling in industrial design. Compared to existing software, GTApprox brings several innovations: a few novel approximation algorithms, several advanced methods of automated model selection, novel options in the form of hints. We demonstrate the efficiency of GTApprox on a large collection of test problems. In addition, we describe several applications of GTApprox to real engineering problems.